Animal Species and Their Evolution - Cain, Arthur J. (Arthur James) (Book collections on Project MUSE., 1993)
Long before Charles Darwin undertook his first voyage, animal taxonomists had begun the scientific classification of animals, plants, and minerals. In the mid-1950s, taxonomist A.J. Cain summarized the state of knowledge about the structure of the living world in his major book Animal Species and Their Evolution. His work remains remarkably current today. Here Cain explains each of the terms by which scientists now classify all animals--from species through genus, family, order, class, and phylum. The work of the modern taxonomist is dependent on the work of paleontologists, field biologist.